A combination of combat experience, early abduction, and severe traumatization fuels appetitive aggression and violence among abductees of rebel war in Northern Uganda. Issue 6 (8th July 2020) - Zeller, Anja C.; Conrad, Daniela; Schneider, Anna; Behnke, Alexander; Pfeiffer, Anett; Blum, Gerrit F.; Wilker, Sarah; Elbert, Thomas; Kolassa, Iris‐Tatjana
Abstract: Individuals who perpetrate violence may likely perceive violence as appealing and infliction of violence to derive pleasure is termed as appetitive aggression . Individuals who were abducted as children into an armed group often experience a higher number of traumatic event types, that is traumatic load and are usually socialized in a violence‐endorsing environment. This study aims to investigate the interaction between age at initial abduction with that of traumatic load, and their influence on appetitive aggression along with perpetration of violent acts by former members of an armed rebel group of both sexes. Semi‐structured interviews were conducted among a target group of formerly abducted rebel‐war survivors (including participants with and without combat experience) from Northern Uganda. Participants included 596 women and 570 men with N = 1, 166 ( M age = 32.58, SD age = 9.76, range: 18–80 years). We conducted robust linear regression models to investigate the influence of age at initial abduction, traumatic load, combat experience, and biological sex on appetitive aggression as well as their perpetrated violent acts. Our study shows, appetitive aggression and the number of perpetrated violent acts were specifically increased in individuals who were abducted young, experienced several traumatic events in their lifetime, and with previous combat experience. For perpetrated violence men showed increased levels whereas for appetitive aggression the association was independent of biological sex. Therefore, early abducted individuals with a higher traumatic load, who have combat experience, need to be given special intervention to prevent any further violence.